2008
DOI: 10.1002/chem.200801582
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Synthesis of β‐Amino Acid Derivatives by the Lewis Base Catalyzed Hydrosilylation of β‐Enamino Esters

Abstract: Optically active b-amino acids are very important chiral building blocks for the synthesis of b-peptides, b-lactams, natural products, and physiologically active substances. [1] Therefore, efficient methods for the synthesis of optically active b-amino acids would be of great value for drug discovery and organic synthesis. Among the approaches to chiral b-amino acids, [2] the most straightforward and atom economic one is catalytic asymmetric reduction of b-enamino esters. Pioneered by Noyori et al., [3a] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(16 citation statements)
references
References 305 publications
(376 reference statements)
0
16
0
Order By: Relevance
“…Zhang and co-workers developed an elegant asymmetric hydrosilylation of b-enamine esters using chiral Lewis base 194 as a catalyst (Scheme 66) [151]. High yields and enantioselectivities (up to 96% ee) were obtained for a diverse scope of b-amino acid derivatives.…”
Section: Chiral Organic Base Catalysismentioning
confidence: 98%
“…Zhang and co-workers developed an elegant asymmetric hydrosilylation of b-enamine esters using chiral Lewis base 194 as a catalyst (Scheme 66) [151]. High yields and enantioselectivities (up to 96% ee) were obtained for a diverse scope of b-amino acid derivatives.…”
Section: Chiral Organic Base Catalysismentioning
confidence: 98%
“…As can be seen in Table 1, we found that catalysts 1a and 1b (Figure 1), which gave good results in the enantioselective hydrosilylation of N-aryl β-enamino esters, [9] exhibited only moderate enantioselectivities in the hydrosilylation of ethyl 2-(4-methoxyphenylimino)-2-phenylacetate (2a) at -10°C in chloroform (Table 1, Entries 1 and 2). Afterwards, we were very gratified to find that catalysts 1c and 1d, which delivered poor ee values in the enantioselective hydrosilylation of N-aryl β-enamino esters, [9] gave much higher enantioselectivities in this case (Table 1, Entries 3 and 4). Inversion of the configuration at C4 of the pyrrolidine ring from R to S only caused a slight drop in ee.…”
Section: Resultsmentioning
confidence: 88%
“…(S)-2, Scheme 2). [5] At around the same time, the Malkov and Kočovský group were able to significantly extend the substrate scope to a-substituted b-enamino esters (3!4, Scheme 3). As shown later by Zhang and coworkers, the identical Lewis base LB1 catalyzes the reduction of monoprotected 1, e.g., with a PMP group at the nitrogen atom, with superb levels of enantiocontrol ( 96 % ee, not shown).…”
mentioning
confidence: 97%
“…As shown later by Zhang and coworkers, the identical Lewis base LB1 catalyzes the reduction of monoprotected 1, e.g., with a PMP group at the nitrogen atom, with superb levels of enantiocontrol ( 96 % ee, not shown). [5] At around the same time, the Malkov and Kočovský group were able to significantly extend the substrate scope to a-substituted b-enamino esters (3!4, Scheme 3). [6,9,10] The a substituent added a stereochemical complication to this reduction but several monoprotected b 2, 3 -amino acids 4 were obtained with excellent syn diastereoselectivity.…”
mentioning
confidence: 97%
See 1 more Smart Citation